ANALYSIS OF DUST STORMS IN ERBIL CITY-IRAQ USING SURFACE OBSERVATIONS AND GIS TECHNIQUES - Abdullah, Rebin Samad (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2026)
Dust storms are a common phenomenon in desert and semi-desert areas, they arise when the wind blows and has the ability to soil grains transfer particles from the Earth’s surface and carry them over distances determined by the wind speed and the size of the particles, when this occurs Winds with a speed between (7-8) of per second and at a height of one meter have the ability to can erode soil and transport it over long distances through wind erosion. However, the geography of the study area distant from desert regions, but it is affected by global environmental changes, like most other regions of the world. Erbil city experiences the phenomenon of dust storms, to measure the amount of dust deposition in Erbil, a special glass surface measuring one meter in length and width, equipped with glass, was used to collect dust particles. A scientific analysis of dust deposition was conducted in 2024 according to the results, the maximum amount of dust deposition recorded in Erbil city was 3.5 grams in September, and the minimum of dust deposition is recorded in May 2024 was 1.2 grams, the total area corresponding to the dust deposition in Erbil in 2024 is approximately 383km, Average dust deposition per square meter in Erbil in 2024: 28.21grams , the Total of dust deposition from Erbil city in 2024: 10.8 tons .for the comparison and analysis of the resulting data, a geographic information system (GIS) is used.